Improving the company’s communication strategy with retailers (Laisvalaikio tyrimai, 2025)
Relevance and novelty of the article. Businesses face an increasingly competitive marketplace every day, and smooth and strong communication with business partners ensures success and stable relationships. Türkeș et al. (2024) argue that trust, cooperation, and communication strengthen relational ties, and the relative embeddedness of social capital is a key factor. In the retail sector, large retail chains are among the most important in the supply chain, they are the link between the production company and the consumer, which means that retail chains determine which products reach the audiences and the volumes in which the products are sold.Communication strategy in trade. According to Sparacino et al. (2024), communication is the means through which a company communicates its objectives and achievements through initiatives. In addition, supermarket chains are strengthening the range of products they offer to the end consumer, they want to present professional and attractive looking products on the shelves of their supermarkets, thus they pay a lot of attention to communicating and maintaining good relationships with the suppliers of the products. This reason may determine the quality of the company’s communication strategy with the retail chains, due to the company’s ability to build strong and long-lasting relationships with its customers. Lacombe et al. (2024) state that communication is a key factor in establishing and maintaining meaningful social relationships. Successful communication with a supplier can lead to greater market positioning and visibility, while retail chains are assured of their partner’s credibility. Karlsson et al. (2023) emphasise that the organisation should strategically manage its supply chain, and embody the behavioural norms required within the organisation. Thus, favourable conditions are guaranteed for both sides. Siemieniako et al. (2025) stress that when it comes to the co-creation of value, the focus is not only on the value of the customer or the supplier, but also on the overall value. On the other hand, inappropriate communication methods can lead to misunderstandings that can challenge or even disrupt transactions, supply chain processes and long-standing partnerships between parties. According to Yadav et al. (2024), failure to strategically adapt different orientations can lead to reputational risks. Communication strategies must adapt to the dynamic business environment and evolving consumer demands. Based on Caferra et al. (2025), employees are not only responsible for serving consumers and making them feel comfortable, but also for solving their problems or doubts related to the company. Therefore, analysing and improving a company’s communication strategy with supermarkets is one of the most relevant topics for long-term partnerships and competitive excellence in the market. According to Troiville (2024), consumer attitudes towards the retailer and word-of-mouth communication individually and consistently mediate the relationship between the retailer’s brand equity and consumer loyalty to the retailer.Research problem. Despite the importance of supermarkets as a decisive point for business development, most companies do not have a specific approach to improving their corporate communication strategy with supermarkets. In Wiktor and Sanak-Kosmowska’s (2021) point of view, competitive strategy is based on the optimal allocation of resources, which allows to gain and maintain a dominant position in the sector. In many cases, companies do not have a clear plan to ensure consistent and effective communication with their business partners, to provide them with stable and consistent communication, and to ensure a mutually smooth coordination of objectives. According to Lundin and Kindström (2023), B2B (business-to-business) companies face new challenges in controlling, managing and creating valuable customer experiences, especially when they rely on digital technologies. This can lead to misunderstandings, delays in business transactions, and highlight the importance of a company’s reputational status in a competitive environment. Poor development of the communication strategy with the large retailers can lead to negative factors towards common objectives, as the retailers may lack clear information, consistency, and strategic knowledge from the company. As Serravalle and Pantano (2023) argue, companies should review the message they send to better communicate the importance they place on consumers and the care they give to both consumers and retail staff. In other words, unprofessional communication between a company and retailers can lead to significant losses, such as not expanding in the business marketplace, deteriorating reputation with other potential business partners, and reducing opportunities for cooperation.The aim of the research was to identify opportunities for improving the company’s communication strategy with retailers, by identifying the main difficulties in cooperation and determining measures to create a more effective communication between business entities.Results. The study revealed that the company’s communication strategy with retail chains is underdeveloped. Various communication channels are used, ranging from emails to face-to-face meetings. Informants identified problems on both the company’s and retail chains’ sides – lack of time, insufficient knowledge, communication often being tactless or informal, and ineffective management of information overload, which reduces efficiency. Proposed solutions include focusing on customer needs, strengthening internal communication, organising live meetings, and adopting more modern communication platforms. It is recommended that the company develop a comprehensive, tailored communication strategy focused on clear objectives and effective interaction with retail networks. It is advisable to implement customer relationship management (CRM) systems and utilise artificial intelligence to improve customer service, automate processes, and increase productivity. Ongoing communication training should be organised, and a new department or roles should be established to engage, train, and motivate employees, ensuring consistent and professional communication both internally and externally.Keywords: communication, trade networks, strategy, B2B (business-to-business), company.